Palladium‐Catalyzed Allenylation/Intramolecular Diels–Alder Reaction of Furans with Propargyl Carboxylates for the Synthesis of Polycyclic Compounds. Issue 17 (28th April 2014) - Wang, Chengyu; Kong, Lingkai; Li, Yanli; Li, Yanzhong
Abstract: A highly efficient palladium‐catalyzed cascade reaction of propargyl carboxylates bearing a furanyl group with organoborons was developed. This methodology offers rapid access to polycyclic Diels–Alder cycloadducts in good to high yields. The thus‐formed oxygen‐bridged products were further converted into anthracene derivatives in a chemoselective manner under mild conditions. Abstract : A highly efficient palladium‐catalyzed cascade reaction of propargyl carboxylates bearing a furanyl group with organoborons offers rapid access to polycyclic Diels–Alder cycloadducts in good to high yields. The thus‐formed oxygen‐bridged products can be further converted into anthracene derivatives in a chemoselective manner under mild conditions.